Food Insecurity and Health Behaviors Among a Sample of Undergraduate Students at an Urban University. Issue 1 (2nd January 2023) - Hussain, Bridget Murphy; Ryan, Rachel; Deierlein, Andrea L.; Lal, Supriya; Bihuniak, Jessica D.; Parekh, Niyati
ABSTRACT: Students at universities are experiencing food insecurity, which may be associated with health behaviors. In a pilot study to build a survey that assesses food insecurity and health behaviors among undergraduates, we distributed the survey before (Wave 1; fall 2019) and during (Wave 2; summer 2020) COVID-19. During Wave 1, 41% of students reported food insecurity and 61% met criteria for poor sleep. In Wave 2, 26% reported food insecurity and 49% met criteria for poor sleep. Students experiencing food insecurity were more likely to report poor sleep. This survey will inform recruitment and design of a scaled-up multi-campus study. (100/100 words)